A Hemispherical Image Sensor Array Fabricated with Organic Photomemory Transistors. Issue 1 (22nd November 2022) - Kim, Yeongin; Zhu, Chenxin; Lee, Wen‐Ya; Smith, Anna; Ma, Haowen; Li, Xiang; Son, Donghee; Matsuhisa, Naoji; Kim, Jaemin; Bae, Won‐Gyu; Cho, Sung Ho; Kim, Myung‐Gil; et al.
Abstract: Hemispherical image sensors simplify lens designs, reduce optical aberrations, and improve image resolution for compact wide‐field‐of‐view cameras. To achieve hemispherical image sensors, organic materials are promising candidates due to the following advantages: tunability of optoelectronic/spectral response and low‐temperature low‐cost processes. Here, a photolithographic process is developed to prepare a hemispherical image sensor array using organic thin film photomemory transistors with a density of 308 pixels per square centimeter. This design includes only one photomemory transistor as a single active pixel, in contrast to the conventional pixel architecture, consisting of select/readout/reset transistors and a photodiode. The organic photomemory transistor, comprising light‐sensitive organic semiconductor and charge‐trapping dielectric, is able to achieve a linear photoresponse (light intensity range, from 1 to 50 W m −2 ), along with a responsivity as high as 1.6 A W −1 (wavelength = 465 nm) for a dark current of 0.24 A m −2 (drain voltage = −1.5 V). These observed values represent the best responsivity for similar dark currents among all the reported hemispherical image sensor arrays to date. A transfer method was further developed that does not damage organic materials for hemispherical organic photomemory transistor arrays. These developed techniques are scalable and are amenable for other high‐resolution 3D organic semiconductor devices. Abstract : The authors develop a photolithographic process to prepare a hemispherical image sensor array using one organic thin film photomemory transistor per pixel. Their organic thin‐film photomemory transistors can achieve linear photoresponse, along with the best responsivity for similar dark currents among all the reported hemispherical image sensor arrays to date.